Efektivitas Bimbingan Kelompok Teknik Homeroom Terhadap Psychological Well-Being Pada Siswa MA Tasywiquth Thullab Salafiyah Kudus - Muhammad Khoirul Riza; Muslikah (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2026)
This study aimed to examine the impact of group guidance using the homeroom technique on improving students’ psychological well-being at the Madrasah Aliyah level. The study focused on the dimensions of psychological well-being proposed by Carol D. Ryff. This research employed a quantitative approach with a quasi-experimental design using a one-group pretest–posttest model The participants were 30 eleventh-grade students who had moderate to low levels of psychological well-being. Data were collected using a psychological well-being scale based on a Likert format, which demonstrated acceptable reliability and Data were analyzed through a normality test and a paired sample t-test. The results showed an increase in the mean score from 72.45 to 86.70, with a statistically significant difference (p < 0.001). indicating a significant difference between pretest and posttest. Therefore, group guidance using the homeroom technique is effective in improving students’ psychological well-being.